Eating behavior, phytoestrogen intake and chronotype in relation with premenstrual syndrome among female college students - Hiya Alfi Rahmah; Adendita Azmi Afiattami; Izzati Nur Khoiriani; Izka Sofiyya Wahyurin (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2025)
Background: Premenstrual syndrome (PMS) is a group of physical, behavioral, and emotional problems that occur before menstruation. Although the exact cause of this illness is unknown, various studies have suggested that it may be brought on by dietary, behavioral, or hormonal changes.